2023
DOI: 10.3389/fcimb.2023.1167827
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of SARS-CoV-2 infection by diet-modulated gut microbiota

Abstract: Coronavirus disease 2019 (COVID-19) caused by SARS-CoV-2 infection has claimed millions of lives since late 2019, yet there are still many unexplored areas in its pathogenesis and clinical outcomes. COVID-19 is a disease that can affects multiple systems, some of which are overlapped with those modulated by gut microbiota, especially the immune system, thus leading to our concentration on analyzing the roles of microbiota in COVID-19 pathogenesis through the gut-lung axis. Dysbiosis of the commensal intestinal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 103 publications
0
5
0
Order By: Relevance
“…Importantly, microbiota might influence the disease severity of COVID-19 in the setting of T2DM through the production of important metabolites, such as SCFAs and TMAO [ 350 ]. As mentioned above, butyrate and other SCFA-producing bacterial spp.…”
Section: Effects Of Nutrition On Gut Microbiota In Individuals With C...mentioning
confidence: 99%
See 1 more Smart Citation
“…Importantly, microbiota might influence the disease severity of COVID-19 in the setting of T2DM through the production of important metabolites, such as SCFAs and TMAO [ 350 ]. As mentioned above, butyrate and other SCFA-producing bacterial spp.…”
Section: Effects Of Nutrition On Gut Microbiota In Individuals With C...mentioning
confidence: 99%
“…These beneficial changes occurred through the inactivation of the NF-Kβ signaling pathway as well as a decreasing expression of ACE2, an important regulator in COVID-19 disease severity [ 361 ]. Taken together, these findings suggest that nutrition may serve an important role in regulating pathophysiologic changes in COVID-19 outcome through the optimization of microbiota-related metabolites [ 350 ]. Therefore, improving dietary intake in individuals with chronic inflammatory diseases such as those with T2DM may improve outcomes when affected by COVID-19.…”
Section: Effects Of Nutrition On Gut Microbiota In Individuals With C...mentioning
confidence: 99%
“…However, the precise mechanisms of chemical and molecular crosstalk are poorly understood [ 79 ]. For example, it has been shown that elevated levels of trimethylamine N-oxide (TMAO) are associated with the pathogenesis of Alzheimer’s disease and are known to result in increased formation of reactive oxygen species and pro-inflammatoy cytokines [ 80 , 81 ]. Production of TMAO is known to be associated with the increased population of Ruminococcus bacteria in Alzheimer’s patients and also been found to be elevated in the gut flora of COVID-19 patients [ 82 , 83 ] providing a potential common link between the two conditions.…”
Section: Perspectivesmentioning
confidence: 99%
“…Metabolites secreted by microbes such as short chain fatty acids (SCFAs) and certain indole derivatives are linked to immune regulation and anti-inflammatory properties. An uncontrolled and dysregulate immune response adds severity to COVID-19 and these metabolites may participate in the modulation of immunological response, reducing excessive inflammation and tissue damage ( Tieu et al., 2023 ; Wang M. et al., 2023 ). Some alpha bacterial strains such as Catenibacterium, Ruminococcus, and Eubacterium produce abundant SCFAs, compared with other delta strains.…”
Section: Microbial Metabolites In Immunological Modulationmentioning
confidence: 99%
“…SCFAs), contributing to the maintenance of balanced gut microbial populations and gut integrity. Similarly, the oral intake of beneficial microbes as supplements (probiotics) facilitates healthy microbial gut counts ( Tieu et al., 2023 ). Several clinical studies have shown the positive impact of adding healthy microorganisms to the gut and their effectiveness can also be reflected in the lung cells, via the described bidirectional pathway ( Table 5 ).…”
Section: Therapeutic Approaches and Future Directionsmentioning
confidence: 99%